Obesity and vascular risk - Lijnen, H. R. (Hämostaseologie, 2009)
Obesity is a common disorder and a known risk factor for vascular thrombotic complications. Development of obesity is associated with extensive modifications in adipose tissue involving adipogenesis, angiogenesis and extracellular matrix proteolysis. Studies using a nutritionally induced obesity model in transgenic mice support a role of the fibrinolytic (plasminogen/plasmin) and matrix metalloproteinase (MMP) systems in these processes. Venous or arterial thrombosis models in obese mice confirm a prothrombotic risk associated with obesity.
Keywords: Obesity; adipose tissue; thrombosis; proteolysis